Organic Mulches An eco-friendly method for pest control - Gill, Harsimran Kaur (Indian Farming, 2015)
Mulching provides enormous benefits that can be utilized not onlyat the national scale but also locally. It is a cheaper alternative for pest management when compared to chemicals and other pesticides. Use of this technique can reduce environmental pollution, pesticide hazards, and toxic wastes.